Bilateral Simultaneous Anterior Ischemic Optic Neuropathy Associated with Sildenafil - Marilita M. Moschos; Ioannis Margetis (Case Reports in Ophthalmology, 2011)
We report a case of simultaneous bilateral nonarteritic anterior ischemic optic neuropathy (NAION) due to sildenafil use. A 55-year-old man with an unremarkable medical history presented simultaneous bilateral NAION 8 months after continuous use of sildenafil 4–5 times a month. At presentation, visual acuity (VA) was 0.7 in the right eye (RE) and 0.9 in the left eye (LE). The visual field showed an inferior altitudinal defect in both eyes and a fundus examination revealed prominent optic disc edema in the RE and a crowded optic disc in the LE. The patient was counseled to discontinue sildenafil, and 3 weeks later VA was 1.0 in both eyes and the optic disc edema in the RE was resolved. However, a visual field defect remained in the RE. Three months later, visual fields were unchanged. To the best of our knowledge, this is the first reported case of simultaneous bilateral NAION due to sildenafil use.